2021
DOI: 10.3389/feduc.2021.759541
|View full text |Cite
|
Sign up to set email alerts
|

Austrian Elementary School Teachers’ Perception of Professional Challenges During Emergency Distance Teaching due to COVID-19

Abstract: Schools around the world have transitioned to emergency distance teaching due to the COVID-19 outbreak. In particular, the first lockdown (in early 2020) came unexpectedly for all actors and stakeholders in Austria. School authorities, parents, students and, above all, teachers were faced with considerable challenges. The aim of the present study is to evaluate the perception of Austrian elementary school teachers about distance teaching during the first lockdown. Using two different qualitative data sets from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 46 publications
3
10
0
Order By: Relevance
“…As predicted, and as highlighted in emerging research internationally (e.g. Phillips et al Woltran et al, 2021), teachers also reported difficulty tracking students' progress and meeting students' wellbeing needs during lockdown, with implications for the education they were able to provide. These concerns often centred on students who were not logging on or submitting work, who did not have the technological resources to engage effectively, or who were emotionally sensitive or vulnerable.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…As predicted, and as highlighted in emerging research internationally (e.g. Phillips et al Woltran et al, 2021), teachers also reported difficulty tracking students' progress and meeting students' wellbeing needs during lockdown, with implications for the education they were able to provide. These concerns often centred on students who were not logging on or submitting work, who did not have the technological resources to engage effectively, or who were emotionally sensitive or vulnerable.…”
Section: Discussionsupporting
confidence: 55%
“…Finally, structural resources available within the role are likely to be important to teachers’ perceptions of their roles during the move to remote learning. In a recent qualitative study, for example, Woltran et al ( 2021 ) asked primary school teachers in Austria about the key professional challenges they faced in remote teaching. Alongside workload concerns, a lack of technical equipment and digital skills were identified.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, these new demands also need to be seen in the context of generally increased stress levels due to the pandemic itself—for example, through health issues in family or oneself, or caretaking responsibilities ( Froehlich, 2021 )—and the probability of increasing them even more ( Bakker et al, 2005 ; Bakker and Demerouti, 2007 ). Also in the Austrian context, a recent study showed that the additional workload and the lack of digital skills are a great burden for teachers ( Woltran et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The access to technical equipment such as digital devices and online resources varies greatly across countries, as well as within the countries, where students living in rural areas or stemming from socio-economically disadvantaged backgrounds (low family SES) were disadvantaged (Huber et al, 2020;Opalka et al, 2020;UNICEF, 2020;OECD, 2020b;Thomas and Allen, 2021). Similarly, students with special education needs (SEN) were severely affected by ERT as those students especially need individualized teaching and support from trained professionals (Goldan et al, 2020;Berasategi Sancho et al, 2021;Woltran et al, 2021). Therefore, it can be said that inclusive teaching was and will continue to be a central condition within online learning, in particular for students at risk (Goldan et al, 2020;Schwab et al, 2020;Woltran et al, 2021).…”
Section: Introductionmentioning
confidence: 99%